Positioning Strategies in Bulgarian Marketing Practice – Results from А Content Analysis of Bulgarian Print Media - Katranjiev, Hristo (Research Papers, 2008)
The paper presents results from a vast content analysis of advertising in Bulgarian print media. The research project was planned and managed by the author but was realized by the help of his students from speciality “Marketing” at The University of National and World Economy. The data has been gathered for 3 years (2003-2006). Due to the students’ help over 40 print media were studied and over 1500 print advertisements were analyzed.As a result from the research project basic positioning strategies (typical for the Bulgarian marketing practice) were identified. These positioning strategies are presented together with numerous real examples of advertisements taken from Bulgarian print media. The strategies also have been discussed from point of view of their matter and application conditions.From theoretical point of view the article traces the connections between basic corporate strategies (after prof. Michael Porter) from one side and positioning strategies from the other. The theoretical work includes also a great deal of work connected with literature research. On the basis of this research the author has presented each positioning strategy in a three-point scheme: (1) definition (What is the essence of each positioning approach?); (2) most frequently observed situations of application of each approach (When to apply each approach); (3) managerial recommendations for empirical application of each positioning approach (How to implement each approach?). In summary the author tries to answer three major questions concerning each positioning approach: What kind of approach?; When to implant it?; How to implement it?